DESIGN OF E-MODULE TEACHING MATERIALS BASED ON LOCAL WISDOM FOR BIPA LEARNING - Setiawan, Deni; Al Yumna Muttaqien, Iqbal; Syakur Al Hamdani, Mohammad; Nuryanti, Mira; Juwanda, Juwanda (Annpublisher, 2024)
This research aims to design teaching materials in e-modules that integrate local wisdom to increase the effectiveness of learning Indonesian for Foreign Speakers (BIPA). In the era of globalization, understanding local culture is important to support a more contextual and authentic language learning process. The e-module developed in this research focuses on introducing and understanding local Indonesian culture, such as customs, traditional arts, and social values. This development model uses the Borg & Gall development model, namely preliminary study, research planning, design development, preliminary field test, revision of limited field test results, main field test, revision of wider field test results, feasibility test, final revision of feasibility test results, and dissemination and implementation of the final product. Data collection at the pre-development stage was carried out using a questionnaire validation instrument. The type of data in this research is qualitative data. Qualitative data was obtained from expert test questionnaire validation in the form of data resulting from comments, criticism, and suggestions in the form of nonverbal data at the pre-development stage.